SKILL MANAGEMENT IMPACT IN INDIAN MSMES TOWARDS SUSTAINABLE CONSUMPTION AND PRODUCTION PATTERNS IN THE CONTEXT OF CSR PRACTICES - Yadav, Madhuri; Baral, Sukanta Kumar (International Journal of Research -GRANTHAALAYAH, 2024)
Upskilling is a prevailing trend in the workplace that provides employees with updated and advanced training programs and opportunities to enhance their skills and bridge skill gaps. Sustainable consumption and production patterns and green CSR practices are pervasive in Indian MSMEs to become a greener economy. The consumer demand for sustainable products is visible across the globe, creating opportunities for Indian MSMEs in the international marketplace. In light of this fact, the present research article aims to analyze the current gap in past studies concerning MSMEs by investigating the correlation between sustainability practices, specifically with respect to sustainable consumption and production patterns, green CSR initiatives, and the performance of MSMEs. This study aims to examine various viewpoints on MSMEs' sustainable business practices, which are a) how sustainable consumption impacts the efficiency of MSMEs, b) the influence of sustainable production patterns on MSMEs' performance, and c) the impact on the efficiency of MSMEs' operations as a result of CSR activities. A self-structured questionnaire has been sent to the MSMEs' owners, managers, directors, and administrative officers through email to conduct the research work. In addition, a structural Equation Model (SEM) was used to sample 130 Indian MSMEs. The study's main findings are that the sustainable consumption and production patterns of skill-based CSR practices impact the efficiency of MSMEs in India. It has also been discovered that their sustainable practices are generating global market opportunities. This study has important implications for MSME owners and policymakers because applying sustainable consumption and production patterns and implementing skill-based CSR practices as sustainable strategies will create a greener economy and positively impact the performance of MSMEs.